The Influence of Political and Economic Factors on Emigration From Russia to Europe - Ryazantsev, Sergey; Bragin, Alexey (Journal of Population and Social Studies [JPSS], 2022)
This research examines the influence and interaction of economic and political factors on the process of emigration from the Russian Federation to European countries (e.g., Finland, Switzerland, and Spain) from 1996 to 2019. According to the theoretical part, we determined that the scale of emigration decreases with an increase in GDP per capita. However, with a sharp increase in GDP at the turn of the 2000s, the emigration from Russia to the selected countries has only increased in what can be considered a phenomenon. Following the theoretical framework, we have determined that this process can be facilitated by some extra variable, which in our case is political freedom. To visualize the process, we observe the indicator of freedom of expression, which moderately declined from 1999 to 2016. As a result of the comparative analysis of migration, economic and political data from OECD, Eurostat, and V-Dem Institute, we determined that due to the deterioration of political freedoms within the country, negative political factors have shifted positive economic growth and affected the increase of emigration scale to the selected European countries.